STATUS HUKUM PENGANGKATAN ANAK BAGI ORANG TUA ANGKAT YANG BELUM TERIKAT TALI PERKAWINAN - Imanuel Tandilangi; Musakkir -; Muhammad Basri (Ilmu Hukum Prima (IHP), 2022)
This study aims to analyze the consideration of adopting children for adoptive parents who are not yet bound by marriage. This research was conducted using empirical research methods. The data obtained, both primary and secondary data, are categorized according to the type of data. Then the data was analyzed using qualitative methods, namely analyzing data related to the problem under study, then selected based on a logical mind to avoid errors in the data analysis process.The results of this study indicate that: : The considerations for adopting a child for single parents include, among others, wanting to have children, heirs; Wants to have friends for himself or his children; Wants to realize a social sense, compassion for others, who are in difficulty living according to their abilities